An Analysis of Code Mixing and Code Switching Used by Students in English Education Department of Mathla’ul Anwar University Banten - Hasanati, Yuyun; Rohimajaya, Nur Azmi; Riandi, Riandi (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2025)
Abstract is This study used a qualitative approach and descriptive-qualitative method to examine code-mixing and code-switching among sixth-semester students in the English Education Program at Mathla'ul Anwar University Banten during the 2022-2023 academic year. Five microteaching videos were analyzed. Data were collected through observation, documentation, and checklists. The study found that Subjects A to E used three types of code-mixing according to Hoofman’s theory: intra-sentential, intra-lexical, and mixing involving pronunciation changes. Based on Poplack’s theory, the types of code-switching observed were tag-switching, inter-sentential switching, and intra-sentential switching. Subject A showed the highest frequency of code-mixing with 30 instances (26 intra-sentential and 4 intra-lexical) and the highest frequency of code-switching with 30 instances (1 tag-switching, 14 inter-sentential, and 15 intra-sentential). Code-mixing and code-switching were influenced by bilingual or multilingual abilities, the need to fit social or situational contexts, and specific communication needs. The study suggested further research in sociolinguistics to better understand these phenomenon. The researcher hoped the findings would be useful for readers, students, and researcher interested in code-mixing and code-switching. Keywords: Code Mixing, Code Switching and Sociolinguistics